Estimación de valores económicos para la producción y caracteres funcionales en el ganado lechero de la parroquia 11 de Noviembre para el establecimiento de los objetivos de mejoramiento genético - Tapia Angueta, Cristian David (2021)
This research was conducted at 11 Noviembre parish, in Latacunga city in the Cotopaxi province, identifying the problems of small milk producers. In the Noviembre parish, all production is established as small producers, and over the years they are the most affected because the official price of milk is set at 0.42 cents. If the demand is lower, they reach costs of up to 0.30 cents, causing low profitability in the sector's farmers. The project is framed in the problems of small producers in 11 November parish, where there are several factors that affect an adequate production of milk, including the genetic problem and economic parameters at the time of feeding their animals, the main impact is to conduct a survey of socio-economic, production cost, type of animal that covers the sector, obtaining these data to draw the guidelines to implement a genetic improvement program in the parish improving the conditions of income to 30 small producers. The determination of the productive parameters to establish a genetic improvement plan in the 11November parish, where the small producer is identified with the economic weight is accentuated in the feeding of dairy cattle being this economic weight the main axis of the low profitability of the producer, accompanied by the low price of milk that intermediaries pay in the sector. In all livestock exploitation, the main reason to engage in it is to obtain economic returns, which is manifested in 100% of small producers in the parish of November 11, however, the lack of attention to these sectors is not profitable to engage in livestock activity, endangering the livestock activity in the parish in projection into the future